J Cancer Immunol 2021
DOI: 10.33696/cancerimmunol.3.057
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Characterization by Flow Cytometry of Chronic Lymphoid Leukemia

Abstract: Introduction: Chronic lymphoid leukemia (CLL) is a malignant proliferative disorder of incompetent mature-looking lymphocytes that accumulate in peripheral blood (PB), bone marrow (BM) and lymphoid tissues. Currently, the flow cytometry (FC) technique has demonstrated its great utility in the immunophenotypic classification of this entity. Objective: To characterize the CLL immunophenotype. Methods: A descriptive, cross-sectional study was carried out to determine the cellular immunophenotype of samples from B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…this result was consistent with that reported by Abbas et al 13 and Starostka et al, 29 CD5 was expressed in the vast majority of CLL patients which was significantly higher than that reported in other MBN patients, also the dim to moderate expression https://doi.org/10.15218/zjms.2023.028 pattern was the most common in both group but significantly higher in CLL than other MBN, similar findings were reported by Marrero et al (95.3%), 33 the frequency of CD23 expression was significantly higher in CLL patients than other MBN patients and the pattern Dim-moderate was the predominant in CLL patients and significantly higher compared with other MBN, these results were comparable with that mentioned by Falay et al 25 and Starostka et al 29 in CLL cases, CD79b expression was significantly lower than that of other MBN cases (55.9% vs 87.5%), while CD79b Dim expression was the predominant pattern in CLL cases. Same findings were reported by Marrero et al, 33 The present study reported negative FMC7 expression in all CLL patients while it was expressed in (53.1%) of other MBN patients, these findings were accordance with the results that documented by Starostka et al 29 in which FMC7 was expressed in (2.9%) of CLL patients, the results of this study about sIgM demonstrating that only (4.4%) of CLL cases had positive sIgM expression whereas it was positively expressed in (37.7%) of other MBN cases, and the difference between these two groups was significant, likewise that reported by Köhnke et al, 34 the current study reported that CD200 was expressed in the vast majority of CLL (97.1%) and in (65.5%) of other MBN cases, this difference was significant, its most frequent expression pattern was moderate in CLL and Dim in other MBN cases in agreement with the results of Sawhney et al 30 CLL patients had significantly higher CD43 expression frequency than that of other MBN patients, which was comparable with that reported in literature, 35 Based on these findings we regard the following markers to have significant role in the differential diagnosis of CLL: CD20, CD5, CD23, CD79b, FMC7, sIgM, CD200, CD43, and CD103. presentations and hematological profile of Iraqi CLL patients were not significantly different from that of previous local and global studies, the distinct immunophenotyping, as well as it has been found that immunophenotyping is a promising method for supporting the clinical and morphological characterization of CLL, also Our study found that a certain immunophenotypic markers which differentiate CLL from other MBN.…”
Section: Final Diagnosissupporting
confidence: 80%
“…this result was consistent with that reported by Abbas et al 13 and Starostka et al, 29 CD5 was expressed in the vast majority of CLL patients which was significantly higher than that reported in other MBN patients, also the dim to moderate expression https://doi.org/10.15218/zjms.2023.028 pattern was the most common in both group but significantly higher in CLL than other MBN, similar findings were reported by Marrero et al (95.3%), 33 the frequency of CD23 expression was significantly higher in CLL patients than other MBN patients and the pattern Dim-moderate was the predominant in CLL patients and significantly higher compared with other MBN, these results were comparable with that mentioned by Falay et al 25 and Starostka et al 29 in CLL cases, CD79b expression was significantly lower than that of other MBN cases (55.9% vs 87.5%), while CD79b Dim expression was the predominant pattern in CLL cases. Same findings were reported by Marrero et al, 33 The present study reported negative FMC7 expression in all CLL patients while it was expressed in (53.1%) of other MBN patients, these findings were accordance with the results that documented by Starostka et al 29 in which FMC7 was expressed in (2.9%) of CLL patients, the results of this study about sIgM demonstrating that only (4.4%) of CLL cases had positive sIgM expression whereas it was positively expressed in (37.7%) of other MBN cases, and the difference between these two groups was significant, likewise that reported by Köhnke et al, 34 the current study reported that CD200 was expressed in the vast majority of CLL (97.1%) and in (65.5%) of other MBN cases, this difference was significant, its most frequent expression pattern was moderate in CLL and Dim in other MBN cases in agreement with the results of Sawhney et al 30 CLL patients had significantly higher CD43 expression frequency than that of other MBN patients, which was comparable with that reported in literature, 35 Based on these findings we regard the following markers to have significant role in the differential diagnosis of CLL: CD20, CD5, CD23, CD79b, FMC7, sIgM, CD200, CD43, and CD103. presentations and hematological profile of Iraqi CLL patients were not significantly different from that of previous local and global studies, the distinct immunophenotyping, as well as it has been found that immunophenotyping is a promising method for supporting the clinical and morphological characterization of CLL, also Our study found that a certain immunophenotypic markers which differentiate CLL from other MBN.…”
Section: Final Diagnosissupporting
confidence: 80%